2015
DOI: 10.3892/ijo.2015.3088
|View full text |Cite
|
Sign up to set email alerts
|

Differential antitumor effects of vitamin D analogues on colorectal carcinoma in culture

Abstract: Colorectal cancer (CRC) is an emerging global problem with the rapid increase in its incidence being associated with an unhealthy lifestyle. Epidemiological studies have shown that decreased levels of vitamin D3 significantly increases the risk of CRC. Furthermore, negative effects of vitamin D3 deficiency can be compensated by appropriate supplementation. Vitamin D3 was shown to inhibit growth and induce differentiation of cancer cells, however, excessive vitamin D3 intake leads to hypercalcemia. Thus, develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 74 publications
0
31
0
Order By: Relevance
“…As in other neoplasms, tissue VDR status may suggest which patients with MM might be candidates for VD supplementation as an adjuvant treatment. In vitro studies in breast cancer, colon cancer and lung cancer have shown that those cell lines that express VDR respond to VD supplementation with an anticarcinogenic effect …”
Section: Discussionmentioning
confidence: 99%
“…As in other neoplasms, tissue VDR status may suggest which patients with MM might be candidates for VD supplementation as an adjuvant treatment. In vitro studies in breast cancer, colon cancer and lung cancer have shown that those cell lines that express VDR respond to VD supplementation with an anticarcinogenic effect …”
Section: Discussionmentioning
confidence: 99%
“…Most recently it was shown that both 20(OH)D3 and 20,23(OH) 2 D3 enhance defense mechanisms against UVB-induced oxidative stress and DNA damage in cultured human keratinocytes [23] and murine skin in vivo [22]. 20(OH)D3 and its hydroxymetabolites also show anti-cancer properties that are cell-lineage dependent [53, 54, 64, 68, 69, 88, 90, 9297]. …”
Section: Biological Activity Of Cyp11a1-derived Vitamin D Hydroxydmentioning
confidence: 99%
“…The hydroxyvitamin D 3 metabolites produced by these pathways, including the major product, 20(OH)D 3 , are biologically active in both in vitro (reviewed in [8]) and in vivo [22] models. Since they are less prone to induce hypercalcemia than 1,25(OH) 2 D 3 [23, 24], they deserve special attention as potential therapeutics for the treatment of leukemia [23], melanoma [10, 11, 25, 26] and colorectal cancer [27]. …”
mentioning
confidence: 99%